The perception, aetiology and clinical assessment of restless legs syndrome and periodic limb movements - Kerr, Samantha Elizabeth (My University, 2013)
Restless Legs Syndrome (RLS) and Periodic Limb Movements (PLM) are common neurological disorders for which the underlying aetiology is not fully understood. Currently RLS and PLM are thought to be caused by a central deficiency of dopamine or other functional abnormalities of the central nervous system. The work included in this thesis investigated different new methods of assessing the sensory and motor features of RLS and PLM, in an attempt to extend our understanding of their aetiology and improve the accuracy of diagnosis of these conditions. The first two studies in the thesis described and characterized the sensations of RLS symptoms, and whether they are influenced by the presence of pain, in an English speaking South African population. The most frequently cited descriptors were different to those used in the current RLS diagnostic criteria. Inclusion of the most commonly used RLS descriptors in the diagnostic criteria may help to improve the accuracy of RLS diagnosis. Patients who experienced painful RLS had greater McGill Pain Questionnaire scores and used different terms to describe their RLS to those that did not have painful RLS sensations. The third project quantified the responses of the Hoffman and patellar reflexes in RLS patients using electromyography and kinematics. The RLS patients exhibited hyporeflexia in the evening compared to the morning, and compared to control participants. This data suggests that RLS is not the result of a global state of hyperexcitability, as the literature suggests, but may reflect more discrete functional abnormalities of the spinal cord. A diurnal variation in the patellar reflex was found, supporting the notion of circadian variations of spinal excitability in RLS patients. The final investigation assessed the sensory qualities (discomfort and pain) of RLS in conjunction with motor activity evoked by using the Suggested Immobilization Test. Despite rating significant levels of discomfort, the majority of the RLS patients did not exhibit PLM; possibly suggesting a disconnect between the sensory and motor components of RLS. In conclusion, it is the major finding of this thesis that inclusion of new assessment techniques for the measurement of sensory and motor features of RLS and PLM provides both new insights and potential clinical tools enhancing our understanding of these disorders.
thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree Doctor of Philosophy. Johannesburg, 2013
Keywords: Restless legs syndrome.; Diseases - Causes and theories of causation.